Stress Level of Mothers with Children with Special Needs - Ima Sukmawati; Elis Noviati; Yuyun Rahayu (Science Midwifery, 2021)
Mothers with children with special needs have a higher stress level than parents with normal children. Mothers usually show psychological symptoms including depression and anxiety which will affect the quality of life of the child. Objective: This study aims to determine the stress level of mothers who have children with special needs at SLB Sindangsari Cikoneng Sindangsari. Methods: The study used a descriptive method with the instrument using a questionnaire. Results: It was found that of the 32 respondents in the moderate stress category, 30 respondents (93.75%) were found. Suggestion: support is needed, especially from the family so that the stress experienced by mothers with children with special needs can be overcome